Proverbs and Sayings in the Poetry of Haji Qadir Alkoy - عبداهلل یاسین ئامێدی; حەیدەر جەوهەر ئەحمەد (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
The literature of folklore occupies a prominent place in the history of Kurdish literature because it is a literature of full of production, so we find that the majority of the poets of the Kurds benefited from this legacy. Haji Qadir is considered one of the most famous poets in this context, especially his use of proverbs in a remarkable way and in his rightful place. To illustrate this, we discussed in this research how to use the proverbs directly and indirectly in his poems, with examples of poetic verses that included it.